2019
DOI: 10.1016/j.sjbs.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi and biochar improves drought tolerance in chickpea

Abstract: Arbuscular mycorrhizal fungi (AMF) inoculation and biochar amendment has been reported to improve growth of several crop plants however their role in stress amelioration individually as well as in combination has not been worked out. This experiment was conducted to evaluate the application of AMF and biochar on the performance of chickpea under drought stress. The treatments included the individual as well as combined treatment of AMF and biochar to drought stressed and normal chickpea plants. Plants inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
92
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(124 citation statements)
references
References 55 publications
29
92
0
3
Order By: Relevance
“…Similar relationships have been described for numerous other plant–mycorrhizal associations (e.g. rose (Abdel‐Salam et al , ), sorghum (Sun et al , ), chickpea H(ashem et al , ), and many tree species (summarized in Brunner et al ()). Plant exudates can also select for specific bacteria that enhance drought protection.…”
Section: Root Exudates As Stress Mediatorssupporting
confidence: 71%
“…Similar relationships have been described for numerous other plant–mycorrhizal associations (e.g. rose (Abdel‐Salam et al , ), sorghum (Sun et al , ), chickpea H(ashem et al , ), and many tree species (summarized in Brunner et al ()). Plant exudates can also select for specific bacteria that enhance drought protection.…”
Section: Root Exudates As Stress Mediatorssupporting
confidence: 71%
“…In the current study, mycorrhizal inoculated seedlings displayed higher Pn, Gs, and Tr, but lower Ci concentrations under both WW and drought stress conditions than their non-mycorrhizal treated counterparts, which was similar in woody species, such as black locust [8], P. trifoliata [66], carob (Ceratonia siliqua L.) [65], and M. hupehensis [3]. Studies have also shown that by increasing leaf area and P content, to regulate the physiological status, AMF optimizes the photosynthetic rate in the host plants [12]. Our results of a higher leaf area and P content in the inoculated seedlings also confirmed this.…”
Section: Discussionmentioning
confidence: 72%
“…One promising management approach is to convert rice straw [1] or rice husk [4] into biochar, which can be suitable source of silicon. Biochar is used as a conditioner to improve soil quality and yield in agricultural systems [3,5,6], enhance soil carbon sequestration potential [1,7,8], enhance nutrient cycles in agricultural lands [3,[9][10][11] and alleviate the harmful effects of drought stress for chickpea, Cicer arietinum L. [12] and soybean Glycine max L. [13]. It also promotes plant growth through improving nutrients uptake and assimilation, improving soil microbial activity [5] and phytohormone synthesis [14].…”
Section: Introductionmentioning
confidence: 99%